Membangun Supply Chain Resilience Dengan Pendekatan Quality Function Deployment (House Of Quality) Guna Menganalisis Langkah Mitigasi Pada PT X - Herdian, Tedy; Sholihah, Sita Aniisah; Badri, Avelya Keysha; Poncotoyo, Wahyu; Suryobuwono, Abdullah Ade (Jurnal Sistem Transportasi & Logistik, 2024)
The shift in route from the Suez Canal to the Cape of Good Hope has led to delays in export shipments, resulting in reduced vessel space allocation and increased shipping costs. This indicates that the company is not effectively implementing supply chain resilience. This study aims to analyze the supply chain resilience at the company, a freight forwarding company in the maritime logistics industry, and provide recommendations for possible mitigation steps. The methodology used in this study is Quality Function Deployment (QFD) with the application of three Houses of Quality (HOQ). HOQ 1 is used to analyze the relationship between customer needs and potential risks, thereby identifying risk priorities. Next, HOQ 2 evaluates the relationship between potential risks and their causes, resulting in prioritized risk causes. Finally, HOQ 3 assesses the relationship between risk causes and mitigation measures, to determine the priority of these measures. The study findings indicate that the top three risk priorities are Document discrepancies and handling errors, Service errors, and Communication tool failures. To enhance supply chain resilience at the company, the recommended mitigation measures are: establishing good communication with customers, implementing a performance assessment system for employees with monthly evaluations, and maintaining effective communication and monitoring with shipping line partners.